REPRESENTATION OF POVERTY IN SOUTH KOREA: A CASE STUDY OF BONG JOON-HO’S PARASITE - Muhammad Iqbal; Gonda Yumitro; Havidz Ageng Prakoso (Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
South Korea’s transformation into a modern industrial nation and leading global economic power is a remarkable example. Even though the economy is developing rapidly, pockets of poverty still exist, so a practical alleviation approach is needed. This journal article examines South Korea’s economic growth from 2019 to 2024, showing its extraordinary transformation from crisis to one of the most influential global economic forces. Additionally, this analysis includes perspectives from Bong Joon-ho’s film “Parasite,” which visually shows the social and economic disparities in South Korea, encouraging thoughts about capitalism, poverty, and social class. Methodologically, this research examines well-known national and international journals focusing on how the “Parasite” conception influences the South Korean economy in overcoming poverty. This film depicts social differences through scenes, settings, and dialogue. Various perspectives are used in this discussion, including global development economics and neoclassical growth theory. The recommendations emphasize that vocational skills development, equitable access to education and health services, and sustainable policy implementation in collaboration with the private sector are all important. Ultimately, this article reveals the message of the film Parasite, which illustrates how difficult it is to deal with poverty in South Korea. It also suggests a broad strategy that combines global development economics with local policies tailored to people’s needs.